AN ANALYSIS OF THIRD SEMESTER STUDENTSâ SKILL OF ENGLISH STUDY PROGRAM IN IDENTIFIYING PLOT AND SETTING OF A MOVIE (TWILIGHT) - Firdausya, Dini; Rahayu, Pipit; Sukma, Dian (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was to know, and analyze the components of plot and setting in English Movieâtwilightâ.The data was being taken from studentsâ skill in identifying plot and setting in English Movieâtwilightâ.The data was taken from the students answer and from the movie itself. The steps in analyzing the data were collecting the data, analyzing the data and display the result of the analysis. In collecting the data, the writer used test by using participant observation. In analyzing the data, the writer was used percentage based on Sudjana (1992).Based on the result of the analysis, it could be concluded that from 34 students in identifying plot and setting, it was found that 18 students (52,9%) were good category, 11 students (32,4%) were fair category, and 5 students (14,7%) were very poor category. There were no students was very good and poor category. It means that the studentsâ skill in identifying plot and setting in English movie was good category (52,9%).